Correlation of N-acetylaspartyl glutamate level in the medial prefrontal cortex with FTND and daily smoking amounts in adult cigarette smokers - Xu, Ke; Yu, Miaomiao; Lin, Liangjie; Xu, Man; Ren, Jianxin; Lv, Qingqing; Zhang, Mengzhe; Han, Shaoqiang; Wang, Weijian; Cheng, Jingliang; Zhang, Yong (Frontiers in Neuroscience, 2025)
BackgroundThe neurotransmitter excitation/inhibition (E/I) balance is critical for maintaining normal brain function, and the contribution of nicotine signaling to homeostasis regulation and maintenance of E/I ratios is only beginning to be understood. Advanced J-edited 1H magnetic resonance spectroscopy (1H MRS) enables reliable detection of overlapped brain metabolite, including the neurotransmitters of glutamate (Glu) and N-acetylaspartyl glutamate (NAAG) and gamma-aminobutyric acid (GABA), etc. The purpose of this study was to explore the changes of neurotransmitters in the medial prefrontal cortex (mPFC) of smokers, so as to understand the potential metabolic mechanism of smoking addiction and make a contribution to the cause of smoking cessation.MethodIn 2022, 45 males aged 40–60 years old were recruited. All subjects underwent routine magnetic resonance imaging (MRI) and the J-edited 1H MRS scans on a 3.0T MRI scanner. The edited spectra were post-processed and quantitatively analyzed using the Gannet tools. Two independent samples t-test was used to analyze the differences in GABA, glutamine/glutamic acid (Glx) and NAAG levels between nicotine addicts and control group; Finally, the spearman standard was used to analyze the correlation between metabolite levels and clinical characteristics assessment scales.ResultsAll measured metabolite levels in the brain mPFC region of smokers showed no significant difference to those of the control subjects. While the NAAG levels with reference to total creatine or water signals in smokers was significantly correlated with daily smoking volume, and the level of NAAG/Cr was potentially correlated with the FTND score.ConclusionsIn this study, we observed that the level of medial prefrontal NAAG in smokers was associated with daily smoking volume. This suggests that the metabolism of NAAG in the brain is related to nicotine, and the balance of glutaminergic system in the brain of smokers may be disrupted.